Issues Affecting the Enhancement of Family and Community security (Islamic Sciences Journal, 2023)
It is not hidden to anyone the importance of the family in all societies as it is the first building block in the formation of society, as it is not possible to imagine a human society without it. From this point of view, the maintenance of the family and maintaining its security is the first step in the right direction to build a safe and cooperative society that contributes to serving itself and supporting societies. Others have civilized values and worldly benefits.
Keywords: Strengthening family security, enhancing community security, reforming the individual, reforming the community, setting a good example.